The Lukan periplus of Paul's third journey with a textual conundrum in Acts 20:15 - M. Wilson (Acta Theologica, 2016)
This article discusses a pericope in Acts 20:6–21:8 recounting the sea portion of Paul’s third journey. Its genre resembles the periplus, and generic features are discussed as well as parallels with other periploi. Paul’s periplus in the Aegean and Mediterranean Seas is presented within a fixed calendar in the Jewish year, and the itinerary’s specifics are detailed. A textual conundrum in Acts 20:15 is discussed as it relates to an anchorage opposite Chios. A lexical discussion of ???????? ???? is presented, and possible translations are reviewed. The article presents a new hypothesis that the Ionian city of Erythrae was the place of the ship’s landing. It closes with a brief history of Erythrae’s significance in the Greco-Roman world and why a stop there by Paul’s coasting vessel was likely during this part of the journey.